Categorisation of goals set using Goal Attainment Scaling for treatment of leg spasticity: a multicentre analysis. Issue 16 (31st July 2019) - Ashford, Stephen; Williams, Heather; Nair, Ajoy; Orridge, Samantha; Turner-Stokes, Lynne
Abstract: Background: Goal-classification of person-centred goals, using Goal Attainment Scaling for leg spasticity treatment. Methods: The study was conducted in two phases: phase I, a retrospective review to evaluate categories of goal set in routine clinical practice. Findings were used to design a goal classification system. Phase II, a multi-centre study to confirm the goal categories. Goals set ( n  = 270) were analysed from data collected at three centres in the UK (one centre for phase I). Goal categories were mapped onto the domains of the World Health Organisation, International Classification of Functioning Disability and Health. Results: One hundred and twenty seven participants were recruited in two cohorts: phase I: 63; phase II: 64. Goal categories using both cohorts were assigned to two domains, each subdivided into three key goal categories: Domain 1 : body structure impairment 121 (44%): (a) pain/discomfort 34 (12%), (b) involuntary movements 20 (7%), and (c) range of movement/contracture prevention 67 (25%). Domain 2 : activity function 149 (56%): (a) passive function (ease of caring for the affected limb) n  = 89 (33%), (b) active function (transfers) 26 (10%), and (c) active function (mobility) 27 (10%), other n  = 7 (3%). Conclusions: Patients individual leg spasticity goals can be grouped into six categories and two domains, which will assist clinicians, patients and cares in setting and evaluating goals in practice. Implications for Rehabilitation: Six goal areas used in clinical goal setting for leg spasticity management were identified, under the two domains: (1) body structure impairment: pain, involuntary movements, and range of movement and (2) activities/function: passive function (ease of caring), active function – transfers or standing and active function – mobility. Categorisation of goals is consistent on repeated evaluation and across different clinical services. Using clinical goals for leg spasticity treatment is an effective method to identify treatment priorities.